Comparative in silico characterization of Klebsiella pneumoniae hypervirulent plasmids and their antimicrobial resistance genes - Negin Bolourchi; Anam Naz; Maryam Sohrabi; Farzad Badmasti (Annals of Clinical Microbiology and Antimicrobials, 2022)
Abstract Background The hypervirulent pathotype of Klebsiella pneumoniae (hvKp) is mainly mediated by large virulent plasmids. It seems that these hypervirulent plasmids (HVPs) are accumulating antimicrobial resistance genes (ARGs) and are turning quickly into drug-resistant hypervirulent hybrids. Therefore, molecular mechanisms involved in this convergence needs to be investigated to control their global spread. Methods In this study, the complete sequence of 79 non-redundant hypervirulent plasmids were retrieved from GenBank and their genetic features, hypervirulence and antimicrobial resistance patterns (AMR) as well as their putative transmission capability were compared using bioinformatics tools. Results The majority of HVPs belonged to clonal complex (CC)23, and sequence type (ST)11. IncFIB and IncHI1B were the most prevalent plasmid replicon types. Out of 79 plasmids, 78 were positive for iutA and iucA. The iucC, iucB and iucD genes were found in 77 plasmids. Almost 26% of the HVPs were potentially conjugative of which 71% carried AGRs. ARGs against beta-lactams, carbapenems, quinolones, aminoglycosides, chloramphenicols, tetracyclines and macrolides were detected in 30% of HVPs. Class 1 integron and prophage structures harboring multiple ARGs were found in eight plasmids. Insertion sequences (IS)6, IS110 and IS1380 appeared to be important genetic elements in transmission of ARGs. Conclusions The high prevalence of iucA and iutA suggests their strong capability for rapid and accurate genetic markers for discrimination of hvKp in the laboratory. This study indicated the important role of mobile genetic elements (MGEs) in the emergence of drug-resistance in hypervirulent strains. The high prevalence of putative conjugative hybrids implies higher incidence of multidrug-resistant (MDR)-hvKp strains in near future.